Kursus Singkat Parafrasa Untuk Menghindari Plagiarisme di Kalangan Sivitas Akademia - Putri, Yuliani Kusuma; Rahmansyah, Sutiadi (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
This community service focusing on paraphrasing workshop to avoid plagiarism is carried out based on the results of research on the academic writing similarity index. Research conducted on students’ theses shows that the students’ thesis similarity index has a high percentage in the theory section. This indicates that most of the theories in the thesis were not written through the paraphrasing stage so that it can be said to be plagiarism. The purpose of this community service is to socialize the importance of paraphrasing to avoid plagiarism, as well as to improve the academics’ paraphasing ability when writing scientific papers. The method used in this workshop is material presentation and cooperative learning. All training activities are carried out online. After the material regarding the procedure for paraphrasing was given, the participants were divided into four different groups and were given some theories by the facilitators which they would paraphrase and then present it in front of all participants and presenters for feedback. The evaluation from the participants regarding this activity was very good and the participants hoped that this activity would become a regular workshop.